PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN APLIKASI MOLEAR (MOBILE LEARNING-AUGMENTED REALITY) TERHADAP HASIL BELAJAR GEOGRAFI KELAS X SMA NEGERI 2 KERINCI - Sukron Operma; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
The development of technology at this time has brought enormous changes to all fields, one of which is in the world of education. Therefore, it is necessary to use technology in learning, so that learning is interactive. One of the uses of technology in the learning process is the emergence of an application MOLE-AR (Mobile Learning-Augmented Reality) as an interactive learning medium. The purpose of this study was to determine the effect of using the MOLE-AR application on student learning outcomes. The method used in this study is a quantitative method, in detail the type of research used is experimental research with the pretest-posttest control group design method. The population of this research is class X using cluster sampling technique, the research sample is class XB and XC SMA Negeri 2 Kerinci. Data collection techniques used are interview techniques for the initial study, and test techniques to collect data on student learning outcomes. As a data analysis technique, researchers used a different test to measure the difference in the effect of using MOLE-AR application learning media and conventional learning media. The findings of this study are that there is a better effect on the use of the MOLE-AR application on student learning outcomes compared to the use of conventional learning media in the form of printed books and blackboards. Then it was also found that the level of effectiveness of the MOLE-AR application was classified as effective, based on the increase in the pretest score to the student's posttest value which was analyzed through the gain value.